Overview of recent advances in the classification of ependymomas in WHO CNS5 classification: Simplified approach to their integrated diagnosis - Rakesh K Gupta; Agrima Sharma; Mehar C Sharma (Indian Journal of Pathology and Microbiology, 2022)
Ependymomas can arise along the entire neuraxis; however, they possess site-specific unique molecular alterations and a methylome pattern which is directly related with the prognostic outcomes. Since 2016, when the updated fourth edition of World Health Organization (WHO) classification of tumors of the central nervous system was published, it has been emphasized to classify ependymomas by anatomic site and molecular signatures associated genetic alterations so that classification of the disease reflects its underlying biology. In continuation, the fifth edition of the WHO classification of CNS tumors introduces major changes, including site-specific molecular profiles as the basis of classifying ependymomas. Furthermore, an integrated tier system of reporting is recommended for better clinical correlation and predicting outcomes. WHO grading can still be included in a specific tier, along with molecular markers.